Effects of translocation on survival and growth of freshwater mussels within a West Gulf Coastal Plain river system. Issue 6 (2nd August 2017) - Tsakiris, Eric T.; Randklev, Charles R.; Blair, Andrew; Fisher, Mark; Conway, Kevin W.
Abstract: Human‐mediated threats have led to the rapid decline of species inhabiting freshwater ecosystems, and among the groups most affected are freshwater mussels of the family Unionidae. As a result, species translocation is increasingly used in conservation programmes, yet experimental evidence documenting the success of this strategy is limited. The goal of this study was to examine the effects of translocation on survival probability, shell growth and body condition of a state‐threatened ( Quadrula houstonensis ) and common ( Amblema plicata ) species of freshwater mussel in the San Saba River, located in a West Gulf Coastal Plain river system, USA. Survival probability estimated from a joint live and dead encounter model was high (> 0.85) and varied by treatment for both species. However, differences in survival probability between resident and transplant treatments were relatively small for A. plicata (0.01) and Q. houstonensis (0.12). Generalized additive mixed models of yearly proportional growth and linear mixed models of Fulton's K index for A. plicata varied by treatment and were lower in transplant treatments. Shell growth of Q. houstonensis was unaffected by translocation; whereas, Fulton's K was higher in the transplant treatment. Methods used to translocate mussels were important factors leading to high survival and limited impacts to shell growth and body condition in this study. Differences in shell growth rate between treatments are attributed to possible differences in habitat quality between sites. Our results demonstrate that A. plicata and Q. houstonensis are tolerant of translocation, despite the broad assumption that translocation is detrimental to mussels. Thus, there is a continuing need to study species' responses to translocation to test and improve the ecological soundness of this strategy, particularly because climate change and other human stressors will exacerbate the need to implement conservation measures such as translocation in future decades.